Factors of Consumer Choice of Universities: The Case of Kazakhstani Education System - Jumasseitova, Assel; Zhappargaliyeva, Madina; Zhappargaliyeva, Ayana; Aben, Aiym; Omirali, Nazym; Saduakas, Dinara (Archives of Business Research, 2025)
This study allows to determine consumer preferences in the process of university selection. The research model is based on qualitative methods, primarily in-depth interviews conducted with 70 respondents that represent various regions of the Republic of Kazakhstan. 11 key factors influencing the choice were identified, from which university reputation and career prospects received the highest evaluations. Moreover, applying the expert-factor analysis method, the total score for each criterion was calculated, which reflects the expressiveness of each factor in the case of Kazakhstan. A deep analysis was conducted to examine the dependence of criteria base on the form of payment: scholarship based versus fee paid; and field of study: technical versus social and humanitarian. The validity of the collected data was supported by the concordance and dispersion coefficients calculations. The results of our research can be useful for universities and educational centers, as well as for subsequent research works in the field of consumer behavior.